TCDD'DE YÜK TAŞIMACILIĞI VE ÜLKE PAZARINDAKİ YERİ ÜZERİNE BİR ÇALIŞMA - DOĞANYILMAZ, ENGİN (Fırat Üniveristesi, 2018)
23 Eylül 1856 tarihinde İzmir-Aydın hattının yapım çalışmalarının başlaması ile Anadolu'da demiryolu macerası başlamıştır. Cumhuriyetin ilk yıllarında demiryollarına gereken önem verilerek bir devlet politikası haline dönüştürülmüş, 1923-1950 yılları arasında yılda ortalama 134 km demiryolu yapılmış, demiryollarının diğer taşımacılık türleri arasındaki yük taşımacılığı payı %68 oranına kadar çıkmıştır. 1950'den sonra II. Dünya Savaşı sonrası durum ve Marshall yardımları sonucu karayolu ağırlıklı ulaşım politikaları uygulanmış, bunun sonucunda 1951-2003 yılları arasında yılda ortalama sadece 18 km demiryolu yapılmıştır. Diğer taşıma türlerinin ihmal edilerek karayollarına ağırlık verilmesi sonucunda demiryollarında yük taşımacılığı payı %4,3 oranına kadar gerilemiştir. Ülkemizde özellikle 2000'li yıllardan sonra demiryollarında önemli gelişmeler kat edilmiş, yılda ortalama 138 km demiryolu hattı yapılarak Cumhuriyet Dönemi hareketlilik tekrar yakalanmış, yolların büyük bölümü yenilenmiş, hızlı tren hatlarının hizmete açılmasıyla sektörün imajı değiştirilmiştir. Dolayısıyla demiryollarının yaklaşık elli yıldır ihmal edilmesinin sonucunda ortaya çıkan sıkıntılar giderilmeye çalışılmaktadır. Bu tez çalışmasında Türkiye'de demiryollarının yıllara göre geçirdiği politikalar incelenmiş; TCDD'nin genel yapısı, yük taşımacılığındaki mevcut durumu ve özellikle son on beş yılda gerçekleşen reformların yük taşımacılığı üzerindeki etkileri, literatür taraması ile seçili yıllar bazında elde edilen sayısal veriler çerçevesinde analizleri yapılarak değişim oranları değerlendirilmiş ve bu bilgiler ışığında demiryolu yük taşımacılığı payının arttırılmasını amaçlayan bazı öneriler sunulmuştur.

The railway adventure of the Anatolia has begun with the start of the construction of railway line between İzmir and Aydın on 23rd of April, 1856. In the early years of the Republic, railways were held with great importance and was turned into a state policy. Moreover, from 1923 to 1950 approximately 134 km of railway was constructed on a yearly basis and the share of transportation via railways, among those of other modes of transportation, increased up to 68%. After 1950, as a consequence of the post Second World War environment and the Marshall Plan Aids, a transportation policy that concentrated on land roads, was applied, which resulted in constructing approximately only 18 km of railway each year between the years of 1951 and 2003. Due to neglecting other modes of transportation and focusing on land roads, the share of transportation via railways decreased to 4.3%. Our country has significantly made progress in terms of railways especially after 2000's by constructing approximately 138 km of railways each year, which enabled regaining the momentum in the railways in the early years of the Republic. Furthermore, an important part of the railways was renovated and with the opening of high-speed rail lines, the image of the sector has been refreshed. Therefore, efforts are now being exerted towards solving the problems that derived from neglecting the railways for almost fifty years. In this study, the policies the railways in Turkey have gone through throughout the years, as well as the overall structure of Turkish State Railways, its current state in freight transportation and the impact of the reforms implemented in the past fifteen years on the freight transportation have been examined. Afterwards, their variation rates were revealed by conducting analysis with the numerical data collected through literature review on a selected yearly basis. In light of this acquired information, suggestions aiming at increasing the share of transportation via railways have been made.
A study on freight transportation handling by the Turkish State Railways and its role within the domestic marketplace
Keywords: Ulaşım